’Ūgārīt wa-Mārī (ṯāniyan): al-’ilāqāt baina ’Ūgārīt wa-Mārī wa-’l-Furāt fī ’l-qarn al-ṯālīt ’ašr - Kūbaih, ’Ānī
Text: kwrbyh; Annie Caubet; Ugarit and Mari (Part Two): Mutual Relations between Ugarit, Mari, and the Euphrates in the 13th Century; ersch. 1986?; in Arabic, translated by Baš?r al-Zuhd?.